2007
DOI: 10.1074/jbc.m705823200
|View full text |Cite
|
Sign up to set email alerts
|

Keratocan and Lumican Regulate Neutrophil Infiltration and Corneal Clarity in Lipopolysaccharide-induced Keratitis by Direct Interaction with CXCL1

Abstract: Reconstitution of keratocan and lumican expression in corneas of Kera؊/؊ and Lum ؊/؊ mice using adeno-keratocan and adeno-lumican viral vectors, respectively, resulted in normal neutrophil infiltration in response to LPS. Immunoprecipitation/Western blot analysis showed that lumican and keratocan core proteins bind the CXC chemokine KC during a corneal inflammatory response, indicating that corneal KSPGs mediate neutrophil recruitment to the cornea by regulating chemokine gradient formation. Together, these da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 25 publications
5
62
0
Order By: Relevance
“…Recent studies using chimeric mice have demonstrated that waves of bone marrow-derived cells invade the cornea in the first few days after epithelial scrape or other corneal injury in the mouse (Wilson et al, 2004;Carlson et al, 2006Carlson et al, , 2007. However, studies have also demonstrated that there are resident CD11b-positive cells present in the unwounded corneal stroma (Mayer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using chimeric mice have demonstrated that waves of bone marrow-derived cells invade the cornea in the first few days after epithelial scrape or other corneal injury in the mouse (Wilson et al, 2004;Carlson et al, 2006Carlson et al, , 2007. However, studies have also demonstrated that there are resident CD11b-positive cells present in the unwounded corneal stroma (Mayer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lumican facilitates innate immune response by binding LPS and CD14, the glycerol phosphatidylinositol-linked cell surface adaptor protein that transfers the LPS signal to toll-like receptor 4 (18). In a corneal injury model neutrophil influx is delayed in the Lum Ϫ/Ϫ mice (19,20). Although this may be partly due to impaired innate immune response, it raises the possibility that lumican may have an additional role in neutrophil migration.…”
mentioning
confidence: 82%
“…Beside the aforementioned studies, there is also evidence for the influence of lumican on inflammatory processes. [69][70][71][72][73] Data regarding the role of other 14 members of SLRP family are sparse. Future studies are needed to explore the molecule-specific affinities to different receptors and orchestration of their downstream signaling events.…”
Section: Biglycan Signaling Bridges Innate and Adaptive Immunitymentioning
confidence: 99%